2014
DOI: 10.5606/kbbihtisas.2014.82160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nasal pack use on surgical success in septoplasty

Abstract: Our study results suggest that nasal pack use does not affect surgical success and complication rates in septoplasty. Pack-free septoplasty with the transseptal suture technique is an effective method in the treatment of septal deviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…In some studies where different packing materials or only sutures were used, no significant results were obtained in terms of bleeding or septal hematoma formation. [9][10][11][12] On the other hand, there are other studies that emphasize the importance of nasal packing. 6 A study comparing the efficacy of nasal packing after septal or turbinate surgery suggested that paraffin gauze or Telfa results in less discomfort and bleeding compared to Merocel, and that Telfa also does not produce granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies where different packing materials or only sutures were used, no significant results were obtained in terms of bleeding or septal hematoma formation. [9][10][11][12] On the other hand, there are other studies that emphasize the importance of nasal packing. 6 A study comparing the efficacy of nasal packing after septal or turbinate surgery suggested that paraffin gauze or Telfa results in less discomfort and bleeding compared to Merocel, and that Telfa also does not produce granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed no difference in bleeding or septal hematoma formation if different packing materials are used or if no packing is used. [8][9][10][11] On the other hand some studies highlighted the importance of nasal packing. [12] A trial comparing the efficacy of nasal packs subsequent to septal or turbinate surgery suggested that packing with paraffin gauze or Telfa resulted in less discomfort and bleeding compared to Merocel.…”
Section: Discussionmentioning
confidence: 99%
“…The negative impacts of these materials on quality of life have been shown in previous studies. [4][5][6][7] In this study, we assessed the efficiency of packfree septoplasty using the NOSE scale. We determined the subjective recovery rate of 81.6%.…”
Section: Discussionmentioning
confidence: 99%